Fixed point results concerning α-F-contraction mappings in metric spaces - Lakshmi Kanta Dey (Applied General Topology, 2019)
In this paper, we introduce the notions of generalized α-F-contraction and modified generalized α-F-contraction. Then, we present sufficient conditions for existence and uniqueness of fixed points for the above kind of contractions. Necessarily, our results generalize and unify several results of the existing literature. Some examples are presented to substantiate the usability of our obtained results.